Serial Gene Expression Profiling of Neural Stem Cells Shows Transcriptome Switch by Long-Term Physioxia from Metabolic Adaption to Cell Signaling Profile - Lena Braunschweig; Jennifer Lanto; Anne K. Meyer; Franz Markert; Alexander Storch (Stem Cells International, 2022)
Oxygen is an essential factor in the cellular microenvironment with pivotal effects on neural development with a particular sensitivity of midbrain neural stem cells (NSCs) to high atmospheric oxygen tension. However, most experiments are still performed at atmospheric O2 levels (21%, normoxia), whereas mammalian brain tissue is physiologically exposed to substantially lower O2 tensions around 3% (physioxia). We here performed serial Affymetrix gene array analyses to detect expression changes in mouse fetal NSCs from both midbrain and cortical tissues when kept at physioxia compared to normoxia. We identified more than 400 O2-regulated genes involved in cellular metabolism, cell proliferation/differentiation, and various signaling pathways. NSCs from both regions showed a low number but high conformity of regulated genes (9 genes in midbrain vs. 34 in cortical NSCs; 8 concordant expression changes) after short-term physioxia (2 days) with metabolic processes and cellular processes being the most prominent GO categories pointing to cellular adaption to lower oxygen levels. Gene expression profiles changed dramatically after long-term physioxia (13 days) with a higher number of regulated genes and more diverse expression patterns when comparing the two NSC types (338 genes in midbrain vs. 121 in cortical NSCs; 75 concordant changes). Most prominently, we observed a reduction of hits in metabolic processes but an increase in biological regulation and signaling pointing to a switch towards signaling processes and stem cell maintenance. Our data may serve as a basis for identifying potential signaling pathways that maintain stem cell characteristics in cortical versus midbrain physioxic stem cell niches.